2010
DOI: 10.1002/da.20734
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality exposure therapy in anxiety disorders: a systematic review of process-and-outcome studies

Abstract: In recent years, virtual reality exposure therapy (VRET) has become an interesting alternative for the treatment of anxiety disorders. Research has focused on the efficacy of VRET in treating anxiety disorders: phobias, panic disorder, and posttraumatic stress disorder. In this systematic review, strict methodological criteria are used to give an overview of the controlled trials regarding the efficacy of VRET in patients with anxiety disorders. Furthermore, research into process variables such as the therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
152
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(164 citation statements)
references
References 51 publications
(119 reference statements)
3
152
1
8
Order By: Relevance
“…Considering the fact that virtual reality offers a safe and non-evaluative environment for the confrontation, training and management of anxious experiences, its use for this specific group may, in fact, be promising, especially because it involves habituation and desensitisation processes. Previous studies 37,42 also indicate positive results with the use of this intervention modality for other phobic-anxious disorders. Therefore, virtual reality is considered an intervention modality which requires studies with a greater methodological refinement and a larger sampling number so that its effectiveness may be proven.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Considering the fact that virtual reality offers a safe and non-evaluative environment for the confrontation, training and management of anxious experiences, its use for this specific group may, in fact, be promising, especially because it involves habituation and desensitisation processes. Previous studies 37,42 also indicate positive results with the use of this intervention modality for other phobic-anxious disorders. Therefore, virtual reality is considered an intervention modality which requires studies with a greater methodological refinement and a larger sampling number so that its effectiveness may be proven.…”
Section: Discussionmentioning
confidence: 82%
“…Once these important methodological considerations are applied, one is able to focus on specific results regarding the interventions, which include more traditional and well-established interventions for different anxiety disorders, such as the cognitive behavioural therapy 36 and virtual reality exposure 37 , as well as interventions that have not been fully endorsed in the literature for use in health care, such as meditation, music therapy, biofeedback, yoga and the Alexander technique.…”
Section: Discussionmentioning
confidence: 99%
“…Uma revisão sistemática da literatura (Meyerbröker & Emmelkamp, 2010), com 23 estudos (n = 608), revelou que em casos de transtornos de ansiedade a VRET produziu melhores resultados do que os observados nos participantes da lista de espera; e teve eficácia semelhante à observada ao se comparar intervenções comportamentais e cognitivo-comportamentais associadas com a exposição à realidade virtual com aquelas sem o componente de exposição mediada por esse tipo de tecnologia. Além disso, verificou-se que a VRET teve impacto na vida dos clientes semelhante ao das psicoterapias clássicas e não houve diferença no número de não adesões ao se comparar a VRET e a terapia de exposição in vivo.…”
Section: Conclusãounclassified
“…Fortunately, these limits stimulated researchers in the field of anxiety disorders to find new means of exposing patients. It led virtual reality to be used in several outcome studies that have shown that exposure conducted in virtual reality is an effective and empirically validated treatment of specific phobias [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, more than 40 clinical trials have been conducted so far (for reviews see [15] to [18]). Although some studies correspond more to pilot or uncontrolled clinical trials, there has been many strong and convincing randomized clinical trials showing that exposure conducted in virtual reality is more effective than no treatment or a waiting list, more effective than some alternative treatments, and no less effective than in vivo exposure [17][18].…”
Section: Introductionmentioning
confidence: 99%